Hydraulic conductivity of compacted zeolites. Issue 6 (June 2013) - Ören, A Hakan; Özdamar, Tugğçe
Hydraulic conductivities of compacted zeolites were investigated as a function of compaction water content and zeolite particle size. Initially, the compaction characteristics of zeolites were determined. The compaction test results showed that maximum dry unit weight (γdmax ) of fine zeolite was greater than that of granular zeolites. The γdmax of compacted zeolites was between 1.01 and 1.17 Mg m −3 and optimum water content (wopt ) was between 38% and 53%. Regardless of zeolite particle size, compacted zeolites had low γdmax and high wopt when compared with compacted natural soils. Then, hydraulic conductivity tests were run on compacted zeolites. The hydraulic conductivity values were within the range of 2.0 × 10 −3 cm s −1 to 1.1 × 10 −7 cm s −1 . Hydraulic conductivity of all compacted zeolites decreased almost 50 times as the water content increased. It is noteworthy that hydraulic conductivity of compacted zeolite was strongly dependent on the zeolite particle size. The hydraulic conductivity decreased almost three orders of magnitude up to 39% fine content; then, it remained almost unchanged beyond 39%. Only one report was found in the literature on the hydraulic conductivity of compacted zeolite, which is in agreement with the findings of this study.